2017
DOI: 10.1021/acs.jpca.7b01844
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 13C Isotopic Labeling Location on Dynamic Nuclear Polarization of Acetate

Abstract: Dynamic nuclear polarization (DNP) via the dissolution method has alleviated the insensitivity problem in liquid-state nuclear magnetic resonance (NMR) spectroscopy by amplifying the signals by several thousand-fold. This NMR signal amplification process emanates from the microwave-mediated transfer of high electron spin alignment to the nuclear spins at high magnetic field and cryogenic temperature. Since the interplay between the electrons and nuclei is crucial, the chemical composition of a DNP sample such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 53 publications
0
28
1
Order By: Relevance
“…scitation.org/journal/jcp to longer preservation time of the hyperpolarized state of the 13 C spins at cryogenic temperatures. 43,65 Our data however suggest that the solid-phase 13 C DNP signal and effective 13 C T 1 relaxation time upon 2 H enrichment of the glassing matrix for trityl-doped 13 C samples do not correlate with one another. This is in contrast to the results of a previous study in which there is a correlation of the maximum solid-phase 13 C DNP signals and 13 C T 1 relaxation times upon intramolecular isotopic substitutions in acetate.…”
Section: Articlecontrasting
confidence: 59%
See 1 more Smart Citation
“…scitation.org/journal/jcp to longer preservation time of the hyperpolarized state of the 13 C spins at cryogenic temperatures. 43,65 Our data however suggest that the solid-phase 13 C DNP signal and effective 13 C T 1 relaxation time upon 2 H enrichment of the glassing matrix for trityl-doped 13 C samples do not correlate with one another. This is in contrast to the results of a previous study in which there is a correlation of the maximum solid-phase 13 C DNP signals and 13 C T 1 relaxation times upon intramolecular isotopic substitutions in acetate.…”
Section: Articlecontrasting
confidence: 59%
“…[38][39][40][41][42] Other DNP works have demonstrated that not all 13 C spins are hyperpolarized with the same efficiency and that the DNP signal is dependent upon the isotopic labeling location of the target nuclei. 43,44 In addition, inclusion of trace amounts of paramagnetic additives such as lanthanides and certain transition metal complexes or nanoparticles in the DNP samples could significantly boost the DNP enhancement. [45][46][47][48][49][50][51][52] Furthermore, isotopic labeling of the other component of the DNP sample, the glassing solvents, could either boost or adversely affect the DNP signal in the frozen state depending upon the EPR linewidth of the free radical polarizing agent used.…”
Section: Introductionmentioning
confidence: 99%
“…Sample II has recently been suggested as a novel lineshape polarimeter, 34 and the location of 13 C spin labels has previously been explored with respect to dDNP performances. 35 There is a major improvement in the observed dCP sequence transfer efficiency and final 13 C polarization for sample II compared with sample I (see Table 3). This is likely associated with the fact that sample II has three directly-bound 1 H nuclear spins, whereas the 1 H nuclear spins in sample I are not directly bonded.…”
Section: C-labelling Strategiesmentioning
confidence: 94%
“…On the other hand, the solid state T 1 values at cryogenic temperatures are several orders of magnitude longer than the liquid state relaxation times . Interestingly, deuteration appears to have a T 1 shortening effect in the solid state in the presence of the free radical . Unfortunately, these long solid state T 1 values cannot be used to preserve the polarization because conventional DNP samples prepared as frozen solutions containing the substrate, polarizing free radicals and glassing agents cannot be extracted from the polarizer as frozen polarized samples without dramatic shortening of the 13 C T 1 in the frozen mixture at low field, apparently due to the presence of the free radical .…”
Section: Limitations Of Current Technologymentioning
confidence: 99%